2020
DOI: 10.1002/ange.202002271
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Synthesis of Dialkyl Ketones from the Coupling of N‐Alkyl Pyridinium Salts with Activated Carboxylic Acids

Abstract: While ketones are among the most versatile functional groups, their synthesis remains reliant upon reactive and low‐abundance starting materials. In contrast, amide formation is the most‐used bond‐construction method in medicinal chemistry because the chemistry is reliable and draws upon large and diverse substrate pools. A new method for the synthesis of ketones is presented here that draws from the same substrates used for amide bond synthesis: amines and carboxylic acids. A nickel terpyridine catalyst coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…A free radical trapping experiment with TEMPO ((2,2,6,6-tetramethylpiperidin-1-yl)oxyl) showed that a radical process was highly likely (Scheme 7a), and this was further verified by electron paramagnetic resonance (EPR) experiments with N-tert-butyl-αphenylnitrone (Scheme 7b). Interestingly, the control experiments with a prepared nickel(II) acyl intermediate (6) and a carboxylic acid (2c) under standard conditions could not successfully produce the target product. Only the decarboxylation byproduct of the carboxylic acid (2c) could be detected (Scheme 7c), suggesting that the radical addition to Ni(II)-species 42,45 in the decarboxylative acylation is less likely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A free radical trapping experiment with TEMPO ((2,2,6,6-tetramethylpiperidin-1-yl)oxyl) showed that a radical process was highly likely (Scheme 7a), and this was further verified by electron paramagnetic resonance (EPR) experiments with N-tert-butyl-αphenylnitrone (Scheme 7b). Interestingly, the control experiments with a prepared nickel(II) acyl intermediate (6) and a carboxylic acid (2c) under standard conditions could not successfully produce the target product. Only the decarboxylation byproduct of the carboxylic acid (2c) could be detected (Scheme 7c), suggesting that the radical addition to Ni(II)-species 42,45 in the decarboxylative acylation is less likely.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of this type of reaction include Friedel-Crafts acylation, 2-3 nucleophilic addition of organometallic compounds to amides 4 and transition metal-catalyzed cross-coupling reactions. [5][6][7][8][9][10] The combination of photoredox/nickel catalysis recently initiated by MacMillan 11 and Molander 12 has led to advances in redoxneutral chemical bond formation. [13][14][15][16][17][18][19][20] In this context, several research groups [21][22][23][24] have reported elegant examples of metallaphotoredox-catalyzed C(sp 3 )-H acylation with amides, anhydrides or activated 2-pyridylthioesters as acyl surrogates.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization First, we focused on the development of asymmetric olefin aryl-acylation. To realize the target reaction, we initially screened various electrophilic acylating agents including the ortho-pyridinyl ester 2a, 43,44 the acid chloride 2a-1, [45][46][47][48][49][50] the acid fluoride 2a-2, 51 the acid anhydride 2a-3, [52][53][54] the thioester 2a-4 55,56 and the activated amide 2a-5, 57 which have been proven to be successful in different cross-electrophile coupling reactions [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] (Table 1). These reactions with the aryl iodide-tethered alkene 1a as the coupling partner were performed in DMA at 40︒C using NiBr 2 • glyme as a precatalyst, the chiral Pyrox L1 as a ligand and Zn as a reductant.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism studies indicated that the reaction proceeds through nickel-mediated bond formation, rather than involving an alkynylmanganese reagent. 111,113 et al 117 et al 115 et al 118 Scheme 15 | (a-d) Nickel-catalyzed reductive acyl cross-couplings via different methods.…”
Section: Alkyl-alkynyl Reductive Cross-couplingsmentioning
confidence: 99%
“…[108][109][110] This has resulted in the development of many synthetic methods. In this regard, nickel-catalyzed reductive ketone formation has become a powerful tool to construct asymmetric ketones (Scheme 15a), and a series of reductive carbonylation reactions have been developed with several acid derivatives, such as acid chlorides, [111][112][113][114] acid fluorides, 115 anhydrides, 116 thioesters, 117 phenolic esters, 118 and in situ activated acids. 119,120 In recent years, tremendous progress was made to utilize stable amides in cross-coupling reactions to synthesize ketones.…”
Section: Reductive Acylation and Carboxylation Reactionsmentioning
confidence: 99%